Cost-effectiveness analysis of Anaprazole versus Ilaprazole for the treatment of duodenal ulcers in China - Ni, Huitong; Shi, Jiaqi; Hu, Ming; Zhou, Naitong; Yang, Shu (Frontiers in Pharmacology, 2024)
Anaprazole, an innovative drug, has shown promise in initial clinical trials for patients with duodenal ulcers (DU) in China. This study aimed to evaluate the potential effects, safety, and cost-effectiveness of Anaprazole compared to Ilaprazole in the treatment of DU and the budgetary impact on the healthcare system. Methods: Two multicentre, randomized controlled trials (ClinicalTrials.gov, NCT04215653 and 2007S00884) were used as data sources. The efficacy and safety of Anaprazole and Ilaprazole were compared using an anchored matching-adjusted indirect comparison (MAIC). A cost-utility analysis (CUA) was performed using a Markov model. A budget impact analysis (BIA) was conducted to evaluate the impact on the expenditure of the Chinese healthcare system. Deterministic and probabilistic sensitivity analyses were undertaken to test the uncertainty.The study findings indicated that Anaprazole and Ilaprazole have similar efficacy and safety in treating DU (OR = 1.05; 95% CI, 0.94-1.01; p = 0.35; OR = 0.63; 95% CI, 0.39-1.08; p = 0.12). The ICUR was 2995.41¥/QALY, which is below the WTP threshold. The CUA results showed that Anaprazole is a cost-effective intervention with a probability of 85% at a given threshold. The results demonstrated strong robustness in the sensitivity analysis. Anaprazole imposed a low burden on the Chinese healthcare budget in the BIA.Compared with Ilaprazole, Anaprazole has similar efficacy, safety, and high costeffectiveness, while also impacting the total expenditure of the healthcare system.